Case Report: Bilateral Biportal Endoscopic Open-Door Laminoplasty With the Use of Suture Anchors: A Technical Report and Literature Review - Zhu, Chengyue; Wang, Jing; Cheng, Wei; Wang, Dong; Pan, Hao; Zhang, Wei (Frontiers in Surgery, 2022)
Background: Unilateral biportal endoscopy (UBE) is a newly developed technique for spine surgery. Owing to the convenience of nerve decompression and compatibility with open surgical instruments under endoscopic guidance, this technique has seen widespread global use. In this study, we first used modified UBE with suture anchor fixation for cervical laminoplasty in a 65-year-old female patient with good clinical outcomes. Methods: We used bilateral biportal endoscopy (BBE) for cervical laminoplasty with suture anchor fixation in a patient with cervical stenosis. Under endoscopic guidance, a bilateral approach was used to make the gutter and lift the lamina door. After the lamina doors were opened, sutures were tied tightly using facia cannula and knot pusher. After confirming the solidarity of the open-door status, the drainage tube was inserted and the incisions were closed. The patient’s pre- and postoperative radiological and clinical results were evaluated. Results: Postoperative Japanese Orthopaedic Association (JOA) and Neck Disability Index (NDI) scores were improved clinically, and cervical canal was decompressed radiologically. Conclusions: BBE laminoplasty combined with suture anchor fixation showed a favorable clinical and radiological result and appears to be a safe and effective technique for cervical stenosis.